व्यतिरेक वितरणका आधारमा डडेल्धुरेली भाषाका वर्ण निर्धारण {Determination of the Phonemes of the Dadeldhura Dialect Based on Contrastive Distribution} - Bhatta, Mohan Prasad (Educational Journal, 2025)
प्रस्तुत लेख व्यतिरेक वा अर्थभेदकतासँग सम्बन्धित रहेको छ। यस लेखको मुख्य उद्देश्य स्वरवर्ण र व्यञ्जनवर्णहरूको सूची प्रस्तुत गरी ती सबै वर्णहरूको विभिन्न व्यतिरेकी युग्मको माध्यमबाट विश्लेषण गर्नु र तिनको परिवेशगत वितरण पहिचान गर्नु रहेको छ। प्रस्तुत अध्ययनमा गुणात्मक अनुसन्धान विधिको अवलम्बन गरिएको छ।प्राथमिक स्रोत अन्तर्गत तथ्याङ्क सङ्कलन नमूना छनोट विधिमा आधारित छ। यस अन्तर्गत अजयमेरू गाउँपालिकाका विभिन्न उमेर समूह, लिंग, जातजाती, पेशा र वर्गका सूचकहरूलाई उद्देश्यपूर्ण नमूना छनोटका रूपमा चयन गरी शब्दसूची, प्रश्नावली, कुराकानी र अन्तर्वार्ताबाट सामग्री सङ्कलन गरिएको छ। यस भाषामा छ वटा स्वरवर्ण र त्रेसठ्ठी वटा व्यञ्जनवर्ण रहेका छन्। स्वरवर्णहरू जब्राको सक्रियता, जब्राको उचाइ र ओठको अवस्थाका आधारमा पदादि, पदमध्य र पदान्तमा व्यतिरेक देखिन्छन्।व्यञ्जनवर्णहरूमा कोमलतालव्य, प्रकम्पति र पार्श्विक, स्वरयन्त्रमुखी र वर्त्स्य, कोमलतालु (स्पर्शी र अल्पप्राण), वर्त्स्य (स्पर्शसङ्घर्षी र अल्पप्राण), वर्त्स्य (स्पर्शी र अल्पप्राण), दन्त्य (स्पर्शी र अल्पप्राण), ओष्ठ्य (स्पर्शी र अल्पप्राण), कोमलतालु (स्पर्शी र अघोष), कोमलतालु (स्पर्शी र सघोष), वर्त्स्य (स्पर्शसङ्घर्षी र अघोष), वर्त्स्य (स्पर्शी र अघोष) मा पदादि, पदमध्य र पदान्त सबै तहमा व्यतिरेक रहेका छन्, भने नासिक्य वर्ण पदादिमा व्यतिरेक देखिँदैन।त्यसै गरी वर्त्स्य र जिह्वाफलक, स्पर्शसङ्घर्षी र जिह्वाफलक, स्पर्श र जिह्वाग्र, स्पर्श र दन्त्य, वर्त्स्य (स्पर्शसङ्घर्षी र महाप्राण), दन्त्य (स्पर्शी र महाप्राण), वर्त्स्य (स्पर्शसङ्घर्षी र सघोष), वर्त्स्य (स्पर्शी र सघोष), ओष्ठ्य (स्पर्शी र सघोष) मा पदमध्य र पदान्तमा व्यतिरेक पाइँदैन।त्यसै गरी वर्त्स्य र जिह्वाग्र, दन्त्य, ओष्ठ्य, स्पर्श र ओष्ठ्य, कोमलतालु (स्पर्शी र महाप्राण), वर्त्स्य (स्पर्शसङ्घर्षी र महाप्राण), ओष्ठ्य (स्पर्शी र महाप्राण), दन्त्य (स्पर्शी र अघोष), ओष्ठ्य (स्पर्शी र अघोष) मा पदान्तमा व्यतिरेक पाइँदैन। {The present article is related to contrast or phonemic distinctiveness. The main objective of this paper is to present a list of vowel and consonant phonemes, analyze them through various contrastive pairs, and identify their contextual distribution. The study adopts a qualitative research design.Under the primary sources, data collection is based on the sampling method. For this purpose, informants from different age groups, genders, castes/ethnicities, occupations, and classes of Ajaymeru Rural Municipality were purposefully selected. The data were collected through word lists, questionnaires, conversations, and interviews. In this language, there are six vowel phonemes and sixty-three consonant phonemes. The vowels show contrast in initial, medial, and final positions based on the activity of the jaw, the height of the jaw, and the position of the lips.Among the consonants, contrasts are found in all positions (initial, medial, and final) in the following categories: palatal, vibrated and lateral, glottal and alveolar, soft palate (plosive and unaspirated), alveolar (affricate and unaspirated), alveolar (plosive and unaspirated), dental (plosive and unaspirated), bilabial (plosive and unaspirated), soft palate (plosive and voiceless), soft palate (plosive and voiced), alveolar (affricate and voiceless), and alveolar (plosive and voiceless). However, nasal sounds do not show contrast in the initial position.Similarly, no contrast is found in the medial and final positions for the following pairs: alveolar and palato-alveolar, affricate and palato-alveolar, plosive and apical, plosive and dental, alveolar (affricate and aspirated), dental (plosive and aspirated), alveolar (affricate and voiced), alveolar (plosive and voiced), and bilabial (plosive and voiced).Likewise, no contrast is found in the final position for the following: alveolar and apical, dental, bilabial, plosive and bilabial, soft palate (plosive and aspirated), alveolar (affricate and aspirated), bilabial (plosive and aspirated), dental (plosive and voiceless), and bilabial (plosive and voiceless).}